Assessment of fungi in soils of sugarcane crops and their potential for production of biomass-degrading enzymes - Egea, Tassia C. [UNESP]; Rodrigues, Andre [UNESP]; Morais, Priscila Atique de [UNESP]; Silva, Roberto da [UNESP]; Gomes, Eleni [UNESP] (Academic Journals, 2014)
Soil management practices are konwn to affect the biomass and enzyme activities of microbial soil communities. To assess whether burning of sugarcane prior to harvesting affects the community of soilborne fungi, we collected soil simples in two sites: burned sugarcane culture prior harvesting (BS) and non-burned sugarcane culture (NBS). A total of 75 filamentous fungal isolates were recovered from soils in both sites. Trichoderma was the most prevalent genus in both sites, followed by Fusarium, Cunninghamella and Aspergillus. The Sorensen's index (0.60) suggested a slight difference in fungi associated with both areas, with high number of fungal isolates found on BB soil. The abundance of Trichoderma isolates in NBS soil was higher than BS soil; however, the abundance of Fusarium, Aspergillus and Cunninghamella was higher in the latter type of soil. In addition, fungi isolated from BS soil showed the highest production of xylanase and laccase in comparision with fungi isolated form NBS soil. Our results indicate that the different types of sugarcane harvesting apparently did not interfere with the diversity of fungal communnities as revealed by culture-dependent methods. In addition, our data indicates the potencial of fungi from soils of sugarcane crops to produce relevant enzymes related to biomass conversion.
Keywords: Culture-dependent analysis; harvest sistem; agriculture residues; biotechnological potential